Effect of Different Probiotic Fermentations on the Quality of Plant-Based Hempseed Fermented Milk - Yingjun Zhou; Yifan Xu; Shuai Song; Sha Zhan; Xiaochun Li; Haixuan Wang; Zuohua Zhu; Li Yan; Yuande Peng; Chunliang Xie (Foods)
This study investigated the effects of three different single-strain probiotics Lactiplantibacillus plantarum XD117, Lacticaseibacillus paracasei LC-37, and Lacticaseibacillus rhamnosus LGG, on the quality of hempseed fermented milk. The main findings were that adding probiotics increased the inhibition rate of α-glucosidase and pancreatic lipase in hempseed fermented milk significantly. Non-targeted metabolomic correlation analysis results confirmed that 14 substances, including three flavonoids, six amino acids and their derivatives, and five short peptides, were positively correlated with the hypoglycemic and hypolipidemic activities of hempseed fermented milk. Furthermore, a total of 59 volatile flavor compounds were identified, including aldehydes, alcohols, ketones, acids, and esters, and the role mapping of different probiotic communities was provided. These results can guide the development of hempseed fermented milk with unique flavor, rich probiotic content, and significant functional characteristics.